Development of interactive learning media assisted by scratch to enhance understanding of rectangle and square concepts - Lioni Anka Monalisa; Arika Indah Kristiana; Arif Fatahillah; Edy Wihardjo; Valydhifa Ailly Aulia; Saddam Hussen; Oluwanife Segun Falebita (Universitas Muhammadiyah Malang, 2025)
The rapid development of technology sparks an increase in educational innovations, one of which is the use of interactive learning media. Interactive learning media is a tool to gradually improves the delivery of mathematics learning materials. This study aims to develop Scratch-assisted interactive learning media to improve students’ conceptual understanding of two-dimensional figures, especially rectangles and squares. This research employed Research and Development (R&D) model proposed by Thiagarajan. Data analysis in this study included analysis of validity, practicality, and effectiveness. A total average of 3.66 for media and 3.7 for test questions was assigned by the three validators, providing strong evidence for media validity. Likewise, strong practicality was evident as indicated by an average score of 87.89% from 28 students. Finally, the analysis marked N – Gain effectiveness of 66% for test results from 28 students, which corroborated that the media is effective. The results of analysis corroborated that interactive learning media assisted by scratch have proven valid, effective, practical, and demonstrate the potential to enhance students' understanding of rectangle and square concept.